(untitled) (Research, Society and Development, 2020)
Diabetes Mellitus (DM) is considered an important public health problem due to high epidemiological indexes and the negative impact brought to society not only in Brazil but also for everyone. Type 1 (DM) is characterized by deficiency absolute insulin, where the carrier through his cells ß pancheaticas stops secreting this hormone for several factors, like viral infection and external environmental factors. Already the (DM) type 2 appears when the organism cannot use properly the insulin it produces, or does not produce insulin enough to control the blood glucose rete. Link this; the presented word has as aim to analyze the profile epidemiological profile of patients with (DM) in the population of state from Piauí in between 2003 and 2012. Was performed a study transversal descriptive retrospective of approach quantitative. Were used disse secondary of the system Hiperdia, made available by DATASUS, in the period records 6,541 cases in (DM), being 74,1% in (DM) type 2 and 25,9% in (DM) type 1. It is concluded that, mainly the (DM) bitwise grievance frequented in the population of state Piauí in the period studied, occurring the bigger number of cases in the year of 2009.thus, the knowledge and information updated from of the epidemiological profile of this population, with dada already available, can assist the professionals of healer to develop targeted actions for the reduction of morbity and mortality.